2023
DOI: 10.3389/fnmol.2023.1123955
|View full text |Cite
|
Sign up to set email alerts
|

Shared miRNA landscapes of COVID-19 and neurodegeneration confirm neuroinflammation as an important overlapping feature

Abstract: IntroductionDevelopment and worsening of most common neurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis, have been associated with COVID-19 However, the mechanisms associated with neurological symptoms in COVID-19 patients and neurodegenerative sequelae are not clear. The interplay between gene expression and metabolite production in CNS is driven by miRNAs. These small non-coding molecules are dysregulated in most common neurodegenerative diseases and COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 270 publications
0
4
0
Order By: Relevance
“…RNA-based medications can include stabilized miRNAs, anti-miRNA (AM, antagomir) and other approaches directed against specific miRNA activators such as NF-kB (p50/p65), using targeted anti-NF-kB (p50/p65) treatment strategies, or any combination of these advanced therapeutics. NV, EX and/or EMV packets containing strategically designed and stabilized miRNA, anti-miRNA (AM), mRNA in conjunction with other therapeutic components and inflammatory mediators and tailored to individual AD patients using precision medicine and predictive, participatory, preventive and personalized (P4) approaches should be useful in the clinical management of AD and other complex neurological disorders that are now urgently requiring effective disease-modifying intervention [ 17 , 35 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 75 , 79 , 80 , 81 , 82 , 100 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-based medications can include stabilized miRNAs, anti-miRNA (AM, antagomir) and other approaches directed against specific miRNA activators such as NF-kB (p50/p65), using targeted anti-NF-kB (p50/p65) treatment strategies, or any combination of these advanced therapeutics. NV, EX and/or EMV packets containing strategically designed and stabilized miRNA, anti-miRNA (AM), mRNA in conjunction with other therapeutic components and inflammatory mediators and tailored to individual AD patients using precision medicine and predictive, participatory, preventive and personalized (P4) approaches should be useful in the clinical management of AD and other complex neurological disorders that are now urgently requiring effective disease-modifying intervention [ 17 , 35 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 75 , 79 , 80 , 81 , 82 , 100 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic complexity and magnitude of gene expression in the human brain and CNS make the elucidation of even fundamental miRNA-mRNA signaling pathways exceptionally challenging, as does the search for reliable biomarkers for neurodegeneration in the periphery. The manipulation of gene expression using miRNA-based strategies and the use of extracellular vesicles for therapeutic delivery should be of great strategic value in the clinical management of AD and related forms of progressive age-related inflammatory neurodegeneration [ 31 , 35 , 50 , 51 , 80 , 81 , 82 , 83 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Specific Features Of Mirna Abundance Speciation and Traffick...mentioning
confidence: 99%
“…In PD, hsa-mir-129-2-3p is a brain-enriched miRNAs that are elevated in the patient's peripheral lymphocytes and most significantly associated with the hub gene. It is suggested that miRNAs may become a potential therapeutic target for infectious diseases such as SARS CoV-2, swine flu, influenza, and the complications of nervous system disease caused by them [ 213 , 214 ]. Although studies have found that specific miRNAs have excellent performance in the treatment and diagnosis of neurodegenerative disease, there are also some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Latini and colleagues showed a functional role for hsa-let7b-5p in modulating levels of ACE2 and DPP4—two receptors that play an important role in the onset and progression of COVID-19 disease—and established that low expression of this miRNA was associated with ACE2 and DPP4 overexpression in naso-oropharyngeal swabs in COVID-19 patients [ 40 ]. Meanwhile, seeking to better understand the mechanism behind neurological symptoms in COVID-19, Trampuž and colleagues highlighted 98 miRNAs that have been implicated in both COVID-19 and one of five neurological disorders [ 41 ]. Together, these studies implicate miRNAs in the human immune response to COVID-19 infection; however, most of them only included patient populations from Australia, Europe and North America, and none examined the effect of genome-wide genetic variation on host miRNA expression during SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%